Metahistory as Public History: On Introducing Metahistorical Perspectives in Events about Events. Issue 375 (4th March 2022) - Innset, Ola
Abstract: This article argues that the introduction of 'metahistorical perspectives' can greatly enrich the practice of public history. Through the example of a series of public events about important historical events held at the National Library of Norway, it is argued that an attention to microhistory, pedagogical theory and especially William Sewell Jr.'s theory of events can be beneficial when programming events for the general public. This focus on 'metahistorical perspectives' in the practice of public history stands in contrast to widely held notions of public history as entailing simplifications and 'dumbing down' of academic knowledge.